Proceedings of the 4th International Conference on Higher Education Advances (HEAd'18) 2018
DOI: 10.4995/head18.2018.8047
|View full text |Cite
|
Sign up to set email alerts
|

Who is even studying journalism to become a journalist?

Abstract: The paper addresses the question why people are entering training programs which disseminate knowledge necessary for becoming part of the journalistic profession and how these motives go along with the intention to become a member of the profession. Therefore it draws on data collected among students in journalism related programs in Austria in 2015 (n=352)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A recent study of Austrian journalism students found, using a factor analysis, that motivations were linked to aspirations, with those motivated by a sense of political and social agency or a journalistic calling / talent more likely to want to work in the field than those who were motivated by pragmatic, employment-driven motives (Prandner and Moosbrugger, 2018). With this in mind, we now turn to examining the dynamics of journalism students' aspirations.…”
Section: Motivations For Studying Journalismmentioning
confidence: 97%
“…A recent study of Austrian journalism students found, using a factor analysis, that motivations were linked to aspirations, with those motivated by a sense of political and social agency or a journalistic calling / talent more likely to want to work in the field than those who were motivated by pragmatic, employment-driven motives (Prandner and Moosbrugger, 2018). With this in mind, we now turn to examining the dynamics of journalism students' aspirations.…”
Section: Motivations For Studying Journalismmentioning
confidence: 97%
“…This sentiment effected course evaluation as well: It was consistently scored lower than others in the program. At the same time, the responsible lecturers were not satisfied with the learning outcomes of the students, as they should prepare students for social scientific work (Prandner & Moosbrugger, 2018). Thus, it was decided to test different ways to improve student performance and overall satisfaction with the course.…”
Section: The Presented Case Study -The Seminar Quantitative Methods Imentioning
confidence: 99%